Groundwater artesian wells allocation: proposing the use of a geographical information system and a dual analytical hierarchical process. - Almomani, Mohammed A.; Alrejjal, Ala'a H.; Khanfar, Aseel F. (Scottish Geographical Journal)
This study proposed a structured approach that incorporates a geographical information system (GIS) with an analytical hierarchal process (AHP) for selecting the best location for drilling new artesian wells, considering water quantity and salinity, aquifer depth, distance to the area of use, the wells interfering, and land characteristics. ArcGIS software was used to manipulate the raw data to generate a thematic layer for each selection criterion. The proposed approach consists of three phases: the first phase applies regular AHP to find the best site in the study area; and the second phase utilizes the raster overlay feature of ArcGIS to find the best zone in the study area to dig a new artesian well. In the third and last phase, AHP compares the first phase best site with a set of random sites within the best-identified zone in the second phase. A case study was used to exemplify the proposed approach. It results in a sensitivity of about 15% of the original criteria weights. The study concludes that the outcomes of this approach are more trustworthy and robust, as compared to relying solely on the AHP method (phase 1) or ArcGIS (phase 2) method.